A travel journal by a preacher during the annual Pentecost prayer meetings in the Dutch Reformed Church: - J.-A. van den Berg (Acta Theologica)
A travel journal by a preacher during the annual Pentecost prayer meetings in the Dutch Reformed Church is an autoethnographic description of, and reflection on historical, geographical, theological, as well as intimate and personal topics. Of prime importance is an auto-ethnographic description of two experiences by the researcher, namely two series of Pentecost prayer meetings which he conducted in May 2024 in two congregations of the Dutch Reformed Church. These two experiences have, as background, the researcher’s personal and collegial relationship with the receiver of the Festschrift, that conveys the academic research they did together over the past few years. Throughout the course of this article, these descriptions are linked to perspectives arising from a collegial relationship with the work of the receiver of the Festschrift. Arising from these reflections, perspectives are provided for the ministry of Pentecost prayer meetings in the Dutch Reformed Church.